Bioinspired adhesive polymer coatings for efficient and versatile corrosion resistance1. Issue 21 (6th March 2015) - Payra, Debabrata; Naito, Masanobu; Fujii, Yoshihisa; Yamada, Norifumi L.; Hiromoto, Sachiko; Singh, Alok
<x xml:space="preserve">Abstract</x> Bioinspired organic polymer is demonstrated for efficient and versatile corrosion resistance. Present method affords a thin, transparent and highly adhesive protective coatings for wide range of structural metals/alloys.